Organic matter oxidation of the Tégulines Clay formation, (Paris Basin, France): Spatial Heterogeneities. (November 2021) - Le Meur, Mathieu; Boussafir, Mohammed; Le Milbeau, Claude; Debure, Mathieu; Claret, Francis; Robinet, Jean-Charles; Lerouge, Catherine
Abstract: Samples of Albian Tégulines Clay outcropping near Brienne-le-Château in the eastern part of the Paris Basin were subjected to a geochemical characterization of organic matter (OM), combining OM bulk Rock-Eval analysis (RE), organic petrography and molecular analysis. In this study, the objective was to investigate the oxidation of natural organic matter in critical zone developed in early reduced marine clay formation. For that purpose, core samples from three boreholes crosscutting the Tégulines Clay formation down to the Greensands were selected. Several meters of Brienne marls preserved Tégulines Clay from atmosphere and therefore from high weathering and high oxidation in AUB240 borehole, whereas Tégulines Clay were weathered in their upper part in AUB1010 and in AUB230 boreholes as a result to their vicinity to the surface. The results showed that the Total Organic Carbon (TOC) contents in all clays are very low, ranging between 0.3 and 0.7 wt%. The RE bulk data and Tmax parameter of OM in preserved Tégulines Clay indicate that the OM is immature. The organic petrography shows a predominance of gel-like amorphous OM preserved by natural sulphurisation in anoxic environments. Organic matter in Tégulines Clay from the AUB230 and AUB1010 boreholes show similar characteristics. The OM at the top of Tégulines Clay contains large amounts of oxidized lignocellulosic debris and has high RE Oxygen-Index values. In the first upper 10 m of the clays, the RE bulk, organic petrography and molecular data revealed oxidative events (high OI and high oxidized debris contents). Below 10 m, the OM is almost preserved. The OM in the reduced marine Tégulines Clay formation is very little functionalized and seems to be slightly reactive but not negligibly with the inorganic fractions in presence of oxygen. Highlights: OM characterization of the Tégulines Clay formation using bulk and molecular data. Vertical variation of the oxidation profile as a result to the vicinity to the surface. First upper 10 m of the clays subjected to oxidative events, below 10 m OM preserved. Spatial variations of the oxidation state due to different topography of the boreholes. OM bulk and molecular techniques are a good association for critical zone studies.